2017
DOI: 10.15282/mohe.v6i2.142
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Traditional Games intervention program in the Improvement of Form One School-Age Children’s Motor Skills Related Performance Components

Abstract: Abstract:As children age, motor performance develops. Motor performance abilities enable children to process information in handling specific task efficiently. Although children develop motor skills in a variety of physical activities, it could be, however, easily achieved when they engage in voluntary activities in conformity with their interests. Traditional games offer the opportunity for children to play and officiate the rules without any constraint. The current study intends to explore the effectiveness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 10 publications
1
12
0
3
Order By: Relevance
“…The result obtained from the current study implies that weight, height, sitting height, armspan, 10 meter run, 20 meter run, 40 meter run, predicted VO2 max and sit and reach were significant variables were highly contributed in fitness youth performance. Current finding concordance to the previous study that emphasized anthropometric component and physical fitness were contributed high variation regarding the performance of sedentary youth [30,31]. The first component from PCA has revealed physical fitness of power, speed and endurance as major physical fitness must be prioritized when assessing current performance of youth.…”
Section: Discussionsupporting
confidence: 88%
“…The result obtained from the current study implies that weight, height, sitting height, armspan, 10 meter run, 20 meter run, 40 meter run, predicted VO2 max and sit and reach were significant variables were highly contributed in fitness youth performance. Current finding concordance to the previous study that emphasized anthropometric component and physical fitness were contributed high variation regarding the performance of sedentary youth [30,31]. The first component from PCA has revealed physical fitness of power, speed and endurance as major physical fitness must be prioritized when assessing current performance of youth.…”
Section: Discussionsupporting
confidence: 88%
“…In the fourth lesson the students were getting used to physical education learning by practicing some traditional games, until the seventh lesson the students' fundamental skills began to improve. Traditional game of physical and motor fitness (agility, speed, balance, and reaction time) should be improved to give information to assist stakeholders such as physical education teacher [21]. Seeing from the development of better student skills until the tenth lesson it can be recommended that traditional games should be effective and be used in physical education learning in elementary schools.…”
Section: Discussionmentioning
confidence: 99%
“…This research was built based on the development of several references which resulted that traditional games were able to increase knowledge, skills in the teaching and learning process as Badu [5] concluded that the implementation of traditional educational training models based on local potential showed that there was an increase of 15.72% in the form of knowledge and the skills of parents of early childhood. In line with Kamal [6], Gipit [7] which states that the social skills of children with the application of traditional games are higher than those who do not apply the game in the learning process.…”
mentioning
confidence: 80%